Current experience and future potential of facilitating access to digital NHS primary care services in England: the Di-Facto mixed-methods study - Gary Abel; Helen Atherton; Jon Sussex; Nurunnahar Akter; Abodunrin Q Aminu; Wiktoria Bak; Carol Bryce; Christopher E Clark; Emma Cockcroft; Hamish Evans; Evangelos Gkousis; Georgia Jenkins; et al. (NIHR Journals Library, 2024)
Background Current National Health Service policy in England encourages enhanced digital access in primary care service provision. In this study, we investigate 'digital facilitation' - that range of processes, procedures and personnel which seeks to support National Health Service primary care patients in their uptake and use of online services. Objectives Identify, characterise and explore the potential benefits and challenges associated with different models of digital facilitation currently in use in general practice which are aimed at improving patient access to online services in general practice in England. Use the resulting intelligence to design a framework for future evaluations of the effectiveness and cost effectiveness of such interventions. Explore how patients with mental health conditions experience digital facilitation and gauge their need for this support. Design Observational mixed-methods study (literature review, surveys, ethnographic observation and interviews); formal synthesis of findings. Setting General practice in four regions of England. Participants Practice survey: 156 staff. Patient survey: 3051 patients. Mental health survey: 756 patients. General practitioner patient survey: 3 million responders. Ethnographic case-studies: 8 practices; interviews with 36 staff, 33 patients and 10 patients with a mental health condition. Stakeholder interviews: 19 participants. Intervention Digital facilitation as undertaken in general practice. Main outcome measures Patient and practice staff reported use of, and views of, digital facilitation. Data sources Surveys, qualitative research; national General Practitioner Patient Survey (2019-22). Review methods Scoping-review methodology applied to academic and grey literature published 2015-20. Results While we did find examples of digital facilitation in routine practice, these often involved using passive or reactive modes of support. The context of COVID, and the necessary acceleration (at that time) of the move to a digital-first model of primary care, shaped the way digital facilitation was delivered. There was lack of clarity over where the responsibility for facilitation efforts lay; it was viewed as the responsibility of 'others'. Patients living with mental health conditions had similar needs and experiences regarding digital facilitation to other patients. Limitations The context of the COVID pandemic placed limitations on the project. Fewer practices responded to the practice survey than anticipated; reconfiguration of general practices to support COVID measures was a key consideration during non-participant observation with social distancing and other measures still in place during fieldwork. Conclusions Digital facilitation, while not a widely recognised concept, is important in supporting the move to a National Health Service with enhanced digital opportunities and enhanced digital access. General practice staff are allocating resources to provide such efforts in general practices in England. The establishment of clear lines of responsibility, the development of digital tools and platforms that work for patients and practice staff, and investment in staff time and training are needed if digital facilitation is to support the intended digital revolution. Future work We did not find one single dominant or preferred model of digital facilitation which might reasonably be considered to form the basis of an intervention to be tested. Rather, there is a need to co-develop such an intervention with patients, general practice staff and relevant policy experts. We outline a framework for a future evaluation of such an intervention. Study registration This study is registered as ResearchRegistry6523 (www.researchregistry.com/browse-the-registry#home/?view_2_search=Di-Facto&view_2_page=1) and PROSPERO CRD42020189019 (www.crd.york.ac.uk/prospero/display_record.php?RecordID=189019). Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR128268) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 32. See the NIHR Funding and Awards website for further award information. Plain language summary Background Online services are common in the National Health Service. This research looked at 'digital facilitation' in general practices. Digital facilitation is about supporting National Health Service patients in their use of online services. We aimed to understand how much digital facilitation is being used by general practices. We also looked at how digital facilitation happens and if it affects the number of people using online services. Methods We looked at previous research to help us understand what approaches have been used to support patients to use online services. We used surveys to ask staff at general practices what they were already doing, and to ask patients about their experiences. We observed digital facilitation in general practices and spoke to patients and staff to help us understand the benefits and challenges of different approaches. We combined findings from the three stages outlined above to identify key aspects of digital facilitation. All stages of our research included discussions with the project's patient advisory group. Key findings We found that digital facilitation is seen as important and has many forms. Most general practices are using passive and reactive types of facilitation. An example of passive facilitation, initiated by the service but not involving direct inter-personal interaction, is the use of text messaging relating to ordering of repeat prescriptions online. An example of reactive facilitation is providing a response to a patient-initiated query regarding online access. There is clear scope to develop a more proactive approach to facilitation that actively engages patients. Our research highlights a lack of clarity over who is responsible for digital facilitation. Different people (patients, staff, policy-makers) often think that the responsibility lies with others. Investment in digital facilitation is needed. Tools and platforms for digital facilitation that meet patients' and general practices' needs should be developed. Scientific summary Background The NHS is facing the increasing demands of a growing and ageing population, technological progress and changing public expectations. Current NHS policy in England encourages enhanced digital opportunities and enhanced digital access in primary care provision. Drivers behind this move include the assumption that online services lead to improved choice, convenience, and ease of access for users, improved triage systems and streamlining of service delivery. In this research, we addressed 'digital facilitation' [digital facilitation (DF)] - 'that range of processes, procedures and personnel which seeks to support NHS patients in their uptake and use of online services'. We investigated the provision by general practices to support access to NHS online primary care services by their registered patients and carers of those patients. Support in accessing and using services is required at all stages: initial registration for online services; subsequent continued use; and navigating the wide range of NHS online provision. Hence, it is important to understand the extent to which approaches to DF are applied, how they are applied, the impact such efforts have on uptake of online services, and how such uptake may affect patient health and access to healthcare information and services. Aims Identify, characterise and explore the potential benefits and challenges associated with different models of DF currently in use in general practice in England which are aimed at improving patient access to online primary care services. Use the resulting intelligence to design a framework for future evaluations of the effectiveness and cost effectiveness of such interventions. Explore how patients with mental health conditions experience DF and gauge their need for this support. Methods The project comprised four interlinked elements. Initially we undertook a scoping review and narrative synthesis of published literature, seeking to understand and characterise the range, effectiveness and cost effectiveness of models of DF for improving access to online services within health.